Jim Crow networks : African American periodical cultures - Dahn, Eurie (Studies in print culture and the history of the book., 2021)
"Scholars have paid relatively little attention to the highbrow, middlebrow, and popular periodicals that African Americans read and discussed regularly during the Jim Crow era-publications such as the Chicago Defender, the Crisis, Ebony, and the Half-Century Magazine. Jim Crow Networks considers how these magazines and newspapers, and their authors, readers, advertisers, and editors worked as part of larger networks of activists and thinkers to advance racial uplift and resist racism during the first half of the twentieth century. As Eurie Dahn demonstrates, authors like James Weldon Johnson, Nella Larsen, William Faulkner, and Jean Toomer wrote in the context of interracial and black periodical networks, which shaped the literature they produced and their concerns about racial violence. This original study also explores the overlooked intersections between the black press and modernist and Harlem Renaissance texts, and highlights key sites where readers and writers worked toward bottom-up sociopolitical changes during a period of legalized segregation"--